Residents and Tourists as a Complementary Target Markets of Outdoor Event Organizes in Terms of Variable Weather Conditions. The Case of the Saint Dominic’s Fair in Poland - BĘBEN, Robert; DEMPC, Izabela; KUCZAMER-KŁOPOTOWSKA, Sylwia (Journal of Environmental Management and Tourism; Vol 12 No 4 (2021): JEMT Volume XII Issue 4(52) Summer 2021, 2021)
The development of technology, climate change as well as the cultural and social changes cause people to change their behavior, modify priorities and adapt to the new situation. Effectiveness and competitiveness, therefore, require up-to-date information on the market participants and factors affecting their behavior. As such, the aim of this article is to illustrate the impact of the weather conditions on participants’ attendance at various urban outdoor events, crucial for a leisure market. The study presents the relationship between the number of residents and tourists visits at the St. Dominic’s Fair in Gdańsk during individual days of the event and the weather conditions (temperature, precipitation, and sunlight intensity). As one of the data illustration methods, mobile phone-base-station logs were used to analyze consumer behavior. The study proved varying behavior of the residents and the tourists participating in the same event under different weather conditions emphasize these two diverse target markets’ complementarities.